2005
DOI: 10.1007/s00167-005-0638-5
|View full text |Cite
|
Sign up to set email alerts
|

Age predicts outcome of high-tibial osteotomy

Abstract: This study compares the predictive value of age at surgery in high tibial osteotomy. Twenty-seven high-tibial osteotomies in patients who are 65 years or older (mean age at surgery 68+/-4 years, follow up 12+/-2 years) were compared to 67 osteotomies in patients younger than 65 years (mean age at surgery 56+/-6 years, follow up 13+/-3) with respect to the outcome by Cox regression analysis. Failure, i.e. endpoint, was defined as implantation of a knee endoprosthesis and assessed by Kaplan-Meier analysis. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 24 publications
0
53
1
5
Order By: Relevance
“…There were several limitations to our study, including its retrospective design and lack of control group. There were a significant number of patients who were lost to follow-up, although over 80% of patients could be included, which is satisfactory when compared with other studies in this area [18,24]. …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There were several limitations to our study, including its retrospective design and lack of control group. There were a significant number of patients who were lost to follow-up, although over 80% of patients could be included, which is satisfactory when compared with other studies in this area [18,24]. …”
Section: Discussionmentioning
confidence: 75%
“…Despite the fact that HTO results show its effectiveness, great debate on risk factors influencing HTO survival is still on-going. Various factors including age, gender, BMI, activity level, and varus angle are claimed to affect the duration of survival [13-18]. Selecting the ideal patient and identifying risk factors that may affect osteotomy longevity is important to obtain satisfactory results with HTO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have supported the finding that older patients have a higher rate of revision following HTO. Trieb et al 36 reported higher rates of revision in patients > 65 years of age, whilst Hui et al 12 reported a hazard ratio for revision of 3.4 in patients over 50 years of age when compared with patients under 50; neither study presented any information on the effect of age on functional outcome. Only one study, a matched-pair study by Kohn et al, 24 has studied the effect of age on functional outcome following HTO.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that a pre-operative BMI higher than 27.5 is a significant risk factor for early failure [25], and patients with BMI over 30 exhibit significantly lower KSS and WOMAC scores 5 years after HTO [28]. Moreover, HTO is not advisable for patients older than 65 years due to the 7.6% increased risk per year of age and the 1.5-fold relative risk of failure compared to younger patients [29]. …”
Section: Discussionmentioning
confidence: 99%